UPAYA INTENSIFIKASI DAN EKSTENSIFIKASI PENDAPATAN ASLI DAERAH MELALUI PENINGKATAN KUALITAS APARATUR PEMERINTAHAN DAERAH - Memen Kustiawan Ikin Solikin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Referring to the Law No. 32 Year 2004 concerning local government, the local autonomy for both district and municipal governments should be implemented based on the decentralization principles: extensive, tangible, and accountable. The availability of budget becomes one of the preconditions in the regional autonomy implementation. This fiscal matter is issued and regulated through the Law No.33 Year 2004 regarding Fiscal Decentralization. In order to administer the local governing, local revenues should be raised in two ways: intensive and extensive. Intensification of local revenues can be accomplished throughmore active, strict, and careful management of expenditures. This effort involvesinstitutional, organizational and personnel commitments. Meanwhile, obtaining new resources of revenues, especially through taxation and retribution, may do the extensiveness of local revenues. However, the way of obtaining the new resources should not be in conflict with the central government policy. To achieve all these, the human resource quality of government apparatus needs to be enhanced through such approaches as education and training, apprenticeship, promotion, regular rotation, job compatibility, and competition-based approach.